FINANCIAL LITERACY, LOCUS OF CONTROL AND FINANCIAL ATTITUDES ON CONSUMPTIVE BEHAVIOR OF ACCOUNTING PROGRAM STUDENTS - Dita Febriana; Nur Lailiyatul Inayah; Ali Muhdor; Fitriyah Kusuma Devi (Jurnal Akuntansi Dan Manajemen, 2025)
The aim of this research is to determine the influence of financial literacy, locus of control and financial attitudes on the consumptive behavior of accounting study program students at Bhayangkara University, Surabaya. This research uses classical assumption test data analysis. The sampling technique used the Slovin formula to obtain 57 respondents. Data collection techniques are in the form of questionnaires. The research results show that financial literacy has a positive and significant effect on student consumption behavior. Locus of control has a positive and significant effect on students' consumer behavior. Financial attitudes have a positive and significant effect on students' consumptive behavior.